When Calling the Police Exacerbates Harm: Exploring the Roles of Intimate Partner Victimization and Women’s Use of Force - Qiu, Xueli (Journal of family violence, 2025)
PurposeIntimate partner abuse and violence has a high incidence rate in the United States. However, it remains underreported to formal agencies, including the police. With a focus on women who had contacted the police at least once, this study explored the complexity of intimate partner abuse and violence experienced between women who contacted the police each time they needed them and those who did not. The study also compared women who used force against abusers and women who did not in terms of their victimization and police utilization.MethodsThis research is part of a longitudinal study of 172 women’s experiences within the U.S. civil protection order system. In-person, structured quantitative interviews were conducted at a safe and convenient location for the participants and focused on participants’ experiences of intimate partner abuse and violence as well as their experiences within the civil and criminal legal systems.ResultsMost participants contacted the police at least once for violence against them. However, over half of participants also had at least one time when they said they needed police intervention but did not contact the police. Women who contacted the police each time they needed them reported less frequent sexual assault and more injuries than women who had not. Also, women who used force against their abusers indicated more frequent physical victimization, sexual victimization, and higher rates of injuries, compared to women who had not. Furthermore, women who used force reported significantly less perceived fairness when they interacted with the police. No group differences were found for age, race, income, and length of relationships.ConclusionThis paper contributes to the literature about police utilization among women experiencing intimate partner abuse and violence. The findings suggest that women’s experiences of victimization and use of force play a role in their decision-making about calling the police, which in turn indicates that the legal system to some extent does not meet these women’s needs. It highlights the importance of empowerment during women’s help-seeking process and the complexity of survivor decision-making.